Formulate and Evaluate, Fast Dissolving thin Film of Metoprolol Succinate - Karan Kumar; Mayank Bansal; Firoz Khan; Vikas Agarwal; Sunil Sain (Journal of Biomedical and Pharmaceutical Research, 2023)
Objective: Metoprolol succinate, which is used to treat cardiovascular disorders, is a strong beta-1 adrenoreceptor blocker with cardio-selective effect but is heavily metabolised in the liver during the first pass. Our goal is to minimise hypertension by creating a film of metoprolol succinate that dissolves quickly. Methods: Metoprolol succinate films that dissolve in the mouth were made utilising a solvent casting technique. HPMC E5 was used as the film-forming agent, PEG400 was used as the plasticizer, and honey was included as the film-modifying agent in the final formulation. HPMC E15 (X1) and honey (X2) concentrations were used as independent variables, whereas disintegration time (DT), tensile strength (TS), and % cumulative drug release (CDR) were used as dependent variables in a 32-full factorial design. Thickness, folding endurance, tensile strength, disintegration time, and drug release were among the criteria used to assess the manufactured films. Results showed that HPMC E15 and honey both positively impacted DT and TS while negatively impacting CDR. Results: The optimum formulation was determined to be the one with a DT of 58.0 ±1.01 seconds, an in vitro drug release of 105.32± 1.55, and a tensile strength of 73.55 ± 1.37 g/cm2. Conclusion: Thus, employing a solvent casting method, a fast-dissolving thin film of Metoprolol succinate was created with effective taste masking and prompt in vitro drug release. Keywords: Metoprolol succinate, Fast dissolving oral film, HPMC E5, Honey, Solvent casting